A pharmacokinetic interaction between cimetidine or ranitidine and lornoxicam. Issue 817 (November 1993) - Ravic, M.; Salas-Herrera, I.; Johnston, A.; Turner, P.; Foley, K.; Rosenow, D. E.
Abstract : Cimetidine 400 mg twice daily significantly increased serum concentrations and reduced apparent oral clearance of lornoxicam 8 mg twice daily in 12 healthy volunteers. Ranitidine 150 mg twice daily produced no significant changes in lornoxicam pharmacokinetics.